Analysis of Student Administrative Service Management at Institut Agama Islam Negeri Curup - Elizah, Tenti; Asha, Lukman; Fathurrochman, Irwan; Hamengkubuwono; Rahman, Abdul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Efficient student administrative services are fundamental to academic success and institutional effectiveness in higher education. This case study investigates the implementation, challenges, and proposed solutions related to student administrative services at IAIN Curup, a religious-based higher education institution in Indonesia. Data were collected from four administrative staff and twelve students through interviews, observations, and document analysis, and were analyzed using an interactive model to capture emerging themes. Findings reveal persistent challenges despite structured procedures and digital tools, including delays, inconsistent implementation of Standard Operating Procedures (SOPs), limited technological capacity, and communication breakdowns. These issues are analyzed through the lenses of service quality models, particularly SERVQUAL, and change management theory, which highlight gaps in reliability, responsiveness, and institutional adaptability. Participants emphasized the urgent need for integrated, user-friendly digital systems, ongoing capacity building, and enhanced leadership engagement—key components of successful digital transformation initiatives. Moreover, inclusive decision-making and transparent communication emerged as organizational enablers of sustainable service reform. This study contributes to the limited scholarship on administrative management in religious higher education settings by revealing how procedural, technological, and cultural dimensions intersect to affect service delivery. Framed within the global shift toward digitalization in higher education, the findings underscore the importance of adaptive leadership and strategic innovation in sustaining administrative transformation. Future research should further explore the long-term organizational impacts of these reforms.